Surface topology of mixing entropy after two-pulse laser ablation of stainless steel - D.D. Tumarkina; O.Ya. Butkovskii; A.V. Bolachkov; A.A. Burtsev (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2023)
The paper presents experiments on crystallization from a melt with an analysis of the morphology of the emerging crystal structures, showing examples of the formation of dendritic crystals. Using energy dispersive X-ray analysis, studies of the microelement analysis of the areas of effect of two pulsed laser beams on the surface of stainless steel have been carried out for irradiation parameters corresponding to the appearance of dendritic structures in the area of effect. It is shown that in the dendritic regions concentrations of all the components of AISI 304 stainless steel are equalized. Estimation of the entropy of mixing from experimental data showed that in the area of surface dendrites or their accumulations, the surface entropy of mixing corresponded to its value for a high-entropy alloy. Based on the maximum entropy production principle, the phase transition temperature was calculated. Although dendritic crystallization should reduce the entropy of the system, experiments show that the entropy of the alloy increases. Preliminarily it can be concluded that this process is associated with a high oxygen content in the region of dendritic crystal formation after laser irradiation. The results presented in this work allow us to conclude that the formation of structures with complex morphology occurs after thermal oxidative ablation.